Das Bergbauernproblem in den österreichischen Alpen. Perioden und Typen der Entsiedlung - Lichtenberger, Elisabeth (ERDKUNDE, 1965)
The discussion of the problem of mountain farming has recently been taken up by a European body which under standably prefers a statistical analysis of factors. This method is, however, insufficient to achieve a more profound appreciation; it needs supplementation by eludidating the manifold influences and interrelationships which have affected the mountain farms within the major historically developed regions of the Austrian Alps. Furthermore the problem must not be viewed in isolation but can only be understood as a part phenomenon within the framework of the total social and economic development of a much more extensive area. Depopulation and agricultural extensivation of mountain regions did not commence in the first place in the industrial era but much earlier, viz. during late medieval times, as a parallel to the well known desertion process in the region of nucleated settlement of Middle Europe; they gained momentum during the flourishing of the pre-industrial manufacture economy in the late 18th century and reached their climax in the laissez faire era after the middle of the 19th century. The process found its expression in two principal types: the Zuhubensystem, acquisition of farms up for disposal as supplementary holdings but used merely in an extensive way, and the Forsthubensystem, the purchase of farms up for sale by persons outside the farming community for their woodland property and for re-afforestation. The latter system became particularly widespread in the eastern, wooded, lower mountains of interior Austria. In its beginnings it was associated with the manufacture of cutlery, scythes and similar iron commodities, supported originally on extensive demesne forests. Subsequently it increased its momentum because of many other interests in woodland and it has remained an active force until today. The Zuhubensystem had its main concentration in the high mountain areas of Salzburg and Tirol where farms had made use of high altitude summer pastures since the Middle Ages and where farms acquired as Zuhube came to be used as a substitute for and supplement to these pastures. Quantitatively less important are special forms within the area of western Tirol where the custom of divided inheritance prevails and where depopulation resulted in a reduction of the number of small holdings going hand in hand with an increase in their size, or another type the transformation of villages into seasonal settlements in Vorarlberg and lastly, genuine land abandonment in ecologically marginal situations. In the entire high mountain parts of western Austria depopulation has at present been halted by the new possibility of additional earnings through the tourist trade; in the eastern parts, however, despite their ecologically more favourable situation, depopulation progresses because of the continuing great interest in woodland owned by farmers.